Analisis Strategi Pemasaran PT. Bank Sumut Kantor Cabang Pembantu Syariah Karya dalam Meningkatkan Jumlah Nasabah Pembiayaan Multiguna - Kartika, Dinda; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
Marketing strategy is a continuation of the form of market introduction, which will be related to what strategy will be used in marketing the product so that it can be accepted in the market. The marketing strategy of Islamic Banks is one of the steps that must be taken in marketing banking products and services as indicated by increased sales. The increase in sales is oriented towards fund-raising and customer-oriented products, improving service quality and increasing fee-based income. The purpose of this study was to determine the marketing strategy of PT. Bank Sumut Sharia Karya Sub-Branch Office in increasing the number of multipurpose financing customers. The research method used in this research is qualitative with descriptive method. The data is collected, compiled, grouped, analyzed, then integrated so that it becomes a clear and focused picture of the problem under study. Is a research method that is carried out by going directly to the object of research studied at PT. Bank Sumut Sharia Karya Sub-Branch Office. Based on the research results, the marketing strategy used by PT. Bank Sumut Sharia Karya Sub-Branch Office in increasing the number of multipurpose financing customers is by conducting Sales Promotion, Personal Selling and advertising which is applied at PT. Bank Sumut Sharia Karya Sub-Branch Office.